Leptin and Serum Lipids among Sudanese Obese In Khartoum State (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
Obesity epidemic is increasing worldwide at an alarming rate in particular in African countries .Obesity among females more than males and its associated with age, sex and blood pressure(1) .Overweight refers to an excess amount of body weight that may come from muscles, bone, fat, and water, while obesity refers to an excess amount of body fat and leads to morbidity and mortality due to hypertension, dyslipidemia, type 2 diabetes ,coronary heart disease, stroke, gallbladder disease, osteoarthritis, sleep  apnea,  respiratory problems  and cancers.(2  ).   The  objective  of  this study  is  to  assess  the  association  of  Cholesterol, Triglyceride and Leptin hormone Levels among Sudanese Obese Subjects in Khartoum state – Sudan. A case-control study was conducted during the period from January 2017 to August 2018. This study including 130 obese Sudanese individual and 50 ages matched apparently healthy volunteer as control. Total cholesterol and TRG were measured by (Mindary BS 380, China) ELISA method was used to measure level of leptin hormone. Data were analyzed by s (IBM, SPSS) version 21. T.test for means and standard deviation, while Pearson’s correlation between study variables. Mean level of BMI,  T. cholesterol,  TRG and leptin hormone  were  significantly  increase  among  obese  subjects  rather than  other  control group, P value  (0.000,  0.000,  0.000) respectively .There was no significant difference in mean of study parameters of the obese group according to gender classification except  leptin hormone  was found significant increase among female group, P.value  (0.005).The  Correlation studies showed positive between BMI(T.CH,TRG,leptin) R.value( 0.352,0.373,0.452) P.value (0.034,0032,0.004) respectively. This study conclude, significant increase in the serum lipids, of total cholesterol, triglycerides and leptin in obese subjects compare with control group, Positive correlation was observed between BMI and  total cholesterol ,triglyceride and leptin hormone.